Glass ceramic and preparation method thereof

By controlling the particle size distribution and process flow of the matrix glass and the crystal nucleating agent, the problem of low production efficiency of microcrystalline glass is solved, and efficient and excellent performance microcrystalline glass preparation is achieved.

CN120647156APending Publication Date: 2025-09-16AVIC (HAINAN) SPECIAL GLASS MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510792116.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

The existing microcrystalline glass production process is complex, resulting in low production efficiency and high costs, making it difficult to achieve large-scale production.

Method used

By controlling the particle size distribution of the matrix glass and the crystal nucleating agent, a closely contacted mixture is formed after mixing. The process of mixing treatment-molding blank making-crystallization treatment is adopted to promote the uniform distribution of the crystal nucleating agent and improve the interface nucleation efficiency, thereby shortening the crystallization cycle.

Benefits of technology

The hardness, strength, thermal stability and impermeability of microcrystalline glass have been significantly improved, a fast and efficient crystallization process has been achieved, the preparation cycle has been shortened and the quality of the finished product has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005450337170000141
    Figure BDA0005450337170000141
  • Figure BDA0005450337170000151
    Figure BDA0005450337170000151
  • Figure BDA0005450337170000152
    Figure BDA0005450337170000152
Patent Text Reader

Abstract

The invention relates to the technical field of glass manufacturing, and provides microcrystalline glass and a preparation method thereof.The microcrystalline glass comprises a product formed by mixing parent glass and a nucleating agent to prepare a blank and then conducting crystallization treatment; wherein in the parent glass, the particle size is smaller than or equal to 2 mm, the mass ratio of the particles with the particle size smaller than 0.075 mm is smaller than 10%, and the mass ratio of the particles with the particle size ranging from 0.09 mm to 0.25 mm is larger than 60%. According to the microcrystalline glass provided by the invention, the parent glass and the nucleating agent are used as raw materials, the contact area between the parent glass and the nucleating agent is increased due to the relatively small particle size of the parent glass, and two phases are promoted to be tightly attached in a mixed blank making process by enhancing surface active sites. On the basis, after full mixing and blank making, the induction effect of the nucleating agent can be fully played, abundant nucleation sites are provided for the subsequent crystallization process, and the interface nucleation capability of the parent glass is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of glass manufacturing technology, and in particular relates to a microcrystalline glass and a preparation method thereof. Background Art

[0002] Glass-ceramics, also known as glass-ceramics, can essentially be considered a composite material of glass and crystal phases. By manipulating key parameters such as the type, size, proportion, and morphology of the crystals, the material can be endowed with diverse performance characteristics. This provides a new path for expanding material performance, and has been fully validated in the development of new products.

[0003] In the development of new glass-ceramic products, the key lies in improving the crystallization ability of the glass itself. Currently, the following two processes are mainly used:

[0004] First, a nucleating agent is added to the glass raw materials and melted, followed by nucleation and crystallization through an adapted cooling gradient during the molding cooling phase. However, this process suffers from long crystallization cycles and high crystallization temperatures, negatively impacting both production efficiency and cost control.

[0005] Second, while utilizing interfacial energy to promote crystallization in a manner similar to sintering, the subsequent cooling phase for shaping and crystallization still requires a specific cooling gradient system. This process requires the glass to undergo two high-temperature treatments and relies on refractory molds to assist in shaping and forming. Due to the mold's large heat capacity, ineffective heat loss increases significantly, further extending production cycles and reducing efficiency.

[0006] Both processes are limited in their complexity or thermal management defects, which restrict the large-scale and efficient production of microcrystalline glass. Summary of the Invention

[0007] The purpose of this application is to provide a microcrystalline glass and a preparation method thereof, aiming to solve the problem of low production efficiency caused by complicated process flow.

[0008] To achieve the above application objectives, the technical solutions adopted in this application are as follows:

[0009] In a first aspect, the present application provides a glass-ceramic, wherein the glass-ceramic comprises a product formed by mixing a matrix glass and a crystal nucleating agent to form a blank, and then subjecting the mixture to a crystallization treatment;

[0010] Among them, in the matrix glass, the particle size is less than or equal to 2 mm, the mass proportion of particles with a particle size less than 0.075 mm is less than 10%, and the number of particles with a particle size of 0.09 mm-0.25 mm accounts for more than 60%.

[0011] In a second aspect, the present application provides a method for preparing glass-ceramics, comprising the following steps:

[0012] According to the glass-ceramics provided in the first aspect, raw material components are provided;

[0013] The mother glass and the crystal nucleating agent are mixed to obtain a mixed material, wherein the particle size of the mixed material is less than 0.425 mm;

[0014] Molding the mixed material to obtain a green body;

[0015] The green body is crystallized to obtain glass-ceramics.

[0016] The glass-ceramics provided in the first aspect of the present application, with matrix glass and crystal nucleating agent as raw materials, by limiting the particle size of matrix glass particles (as described above), significantly improves its specific surface area and reactivity. Smaller particle size not only increases the contact area between matrix glass and crystal nucleating agent, but also promotes the two phases to achieve close fit in the mixed blank making process by enhancing surface active sites. On this basis, after fully mixing blank making, crystal nucleating agent is able to be relatively evenly distributed in the matrix glass particle gap, effectively improving interface nucleation efficiency. This uniformly dispersed system can give full play to the inductive effect of crystal nucleating agent, provide abundant nucleation sites for subsequent crystallization process, significantly enhance the interface nucleation ability of matrix glass, effectively improve the nucleation efficiency of crystal nucleus and the growth rate of crystal, while achieving the comprehensive improvement of glass-ceramics hardness, strength, thermal stability and impermeability, and show excellent performance in dimensions such as hardness, density, thermal stability and mechanical strength.

[0017] The preparation method of microcrystalline glass provided in the second aspect of the present application adopts the processing technology of "mixing treatment-molding blank-crystallization treatment": first, the matrix glass and the crystal nucleating agent are mixed, then the blank is obtained by molding treatment, and finally the microcrystalline glass is obtained by crystallization treatment. On the one hand, the crystal nucleating agent is more evenly distributed between the particles of the matrix glass through the mixing treatment, which significantly improves the fit between the two. In the subsequent crystallization process, the crystal nucleating agent can serve as a nucleation site, increase the interface nucleation ability of the matrix glass, and promote the uniform formation of crystals inside the matrix glass. At the same time, the evenly distributed crystal nucleating agent can also inhibit the excessive aggregation of crystal nuclei in local areas, reduce the risk of uneven grain size due to spatial competition during crystal growth, promote the uniform germination and orderly growth of crystal nuclei inside the matrix glass, and help to obtain microcrystalline glass with uniform microstructure and excellent mechanical properties. glass; on the other hand, the mixed material obtained after the mixing process has a specific particle size, specifically, the particle size is less than 0.425 mm. The smaller particle size gives it a significantly increased specific surface area and higher surface free energy, which greatly improves the reactivity of the mixed material. In the subsequent crystallization process, the interface reaction efficiency between the nucleating agent and the matrix glass is greatly improved, which not only accelerates the induction and growth of the crystal nucleus, but also promotes the uniform transformation of the crystal phase through efficient material transfer and energy exchange, thereby realizing rapid and efficient crystallization of the matrix glass, significantly shortening the preparation cycle and improving the quality of the finished product. DETAILED DESCRIPTION

[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain this application and are not intended to limit this application.

[0019] In this application, the term "and / or" describes the relationship between associated objects, indicating that three possible relationships exist. For example, A and / or B can represent: A exists alone, A and B exist simultaneously, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0020] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0021] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0022] The terms used in the embodiments of the present application are for the purpose of describing specific embodiments only and are not intended to limit the present application. The singular forms "a", "an", "the" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise.

[0023] The weights of the relevant components mentioned in the examples of this application may not only refer to the specific content of each component, but also represent the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the examples of this application, it is within the scope disclosed in the examples of this application. Specifically, the mass described in the examples of this application may be a mass unit known in the chemical industry, such as μg, mg, g, kg, etc.

[0024] The terms "first" and "second" are used solely for descriptive purposes to distinguish objects, such as substances, from one another and should not be understood to indicate or imply relative importance or to implicitly specify the quantity of the technical features being referred to. For example, without departing from the scope of the embodiments of this application, a first XX may also be referred to as a second XX, and similarly, a second XX may also be referred to as a first XX. Thus, features defined as "first" or "second" may explicitly or implicitly include one or more of such features.

[0025] In a first aspect, the present invention provides a glass-ceramic. Specifically, the glass-ceramic includes a product formed by mixing a matrix glass and a crystal nucleating agent to form a blank, and then subjecting the mixture to a crystallization treatment.

[0026] Among them, in the mother glass, the particle size is less than or equal to 2 mm, the mass proportion of particles with a particle size less than 0.075 mm is less than 10%, and the number of particles with a particle size of 0.09 mm-0.25 mm accounts for more than 60%.

[0027] The sieving method can be used to calculate the mass proportion of particles of a specific particle size in the matrix glass. Specifically, the aperture corresponding to the 10-mesh sieve is 2mm. If the particle size is less than or equal to 2mm, it means that all particles should completely pass through the 10-mesh sieve hole, and no particles should remain on the sieve surface. The aperture corresponding to the 200-mesh sieve is 0.075mm. If the mass proportion of particles with a particle size less than 0.075mm is less than 10%, it means that the mass proportion of particles passing through the 200-mesh sieve is less than 10%. The aperture corresponding to the 60-mesh sieve is 0.25mm, and the aperture corresponding to the 160-mesh sieve is 0.09mm. The mass proportion of particles with a particle size of 0.09mm to 0.25mm is greater than 60%, which means that the mass proportion of particles that cannot pass through the 160-mesh sieve but can pass through the 60-mesh sieve (particle size 0.09mm to 0.25mm) is greater than 60%.

[0028] The crystals in glass-ceramics are formed through controlled crystallization of glass, making controlled crystallization the foundation of glass-ceramics production. The glass crystallization process involves two steps: nucleation and crystal growth. The ability to crystallize depends on the nucleation rate (the number of nuclei formed per unit volume of molten glass per unit time) and the crystal growth rate (the scale of crystal growth per unit time). Therefore, the nucleation and crystal growth processes are key to achieving controlled crystallization. Precise control of these two processes allows the glass to form crystalline phases of a specific size and quantity, endowing the glass-ceramic with the desired microstructure and properties.

[0029] This application establishes a deep correlation between the raw material properties and the crystallization process by selecting a matrix glass and a crystal nucleating agent of a specific particle size as raw materials, as follows:

[0030] In the technical solution of this application, matrix glass and a nucleating agent are the primary raw materials. By limiting the particle size of the matrix glass (as described above), the matrix glass is endowed with a large specific surface area and high reactivity. The smaller particle size not only significantly increases the contact area between the matrix glass and the nucleating agent, but also, by enhancing the surface active sites, promotes close adhesion between the two phases during the mixing and molding process.

[0031] Due to the increase in the contact area between the matrix glass and the nucleating agent, the interfacial energy is significantly increased, which is conducive to making the system more prone to phase separation and forming dense phase interfaces. These interfaces provide rich heterogeneous sites for subsequent nucleation. The large number of phase interfaces generated by phase separation not only increases the entropy of the system by increasing the total interface area, but also further reduces the overall free energy through the reconstruction of the energy state at the interface (such as local charge matching and atomic arrangement adaptation), forming a thermodynamic environment conducive to nucleation. Under low free energy conditions, the critical nucleation work required for crystal nucleation is significantly reduced, and the nucleation rate is increased accordingly; at the same time, the phase interface, as a high-energy active area, can adsorb ions in the melt for directional aggregation, shorten the ion diffusion path, and simultaneously promote the growth of crystal nuclei, ultimately achieving precise control of the size and number of crystal phases.

[0032] Since the matrix glass has a specific size, which means that the matrix glass surface has more defects, therefore, the characteristic that the defects on the matrix glass surface are easy to nucleate at the interface is utilized, that is, the catalytic effect of the particle surface on crystallization is utilized, and the self-catalytic effect of small particles of matrix glass promoting the crystallization of larger particles through heterogeneous reactions is utilized, thereby promoting the nucleation and crystallization of the matrix glass on the surface of the particles during the crystallization treatment, thereby increasing the crystal growth rate.

[0033] Moreover, after being fully mixed and formed into blanks, the nucleating agent is dispersed in the gaps between the matrix glass particles in a more uniform state. Since it fits tightly to the particle surface of the matrix glass, a good interface interaction is formed between the nucleating agent and the matrix glass. This close contact enables the nucleating agent to fully exert its inductive effect, significantly reducing the activation energy required for nucleation, and increasing the rate of nucleation formation and the growth rate of crystals. Since the nucleating agent is relatively evenly distributed on the surface of the matrix glass particles, the risk of uneven grain size due to space competition during crystal growth (such as the local appearance of coarse grains or amorphous glass phase-enriched areas) is reduced, and the uniform germination and orderly growth of the nuclei inside the matrix glass are promoted, which helps to obtain microcrystalline glass with uniform microstructure and excellent mechanical properties, and achieves a comprehensive improvement in the hardness, strength, thermal stability and impermeability of the microcrystalline glass, and exhibits excellent performance in terms of hardness, density, thermal stability and mechanical strength.

[0034] In practical applications, there is no specific requirement for the mother glass material. Ordinary float glass, soda-lime container glass, aluminosilicate flat glass and other glassy solids can be selected, and mixtures of the above materials can also be used.

[0035] For example, in the matrix glass, the mass proportion of particles with a particle size of 0.09 mm-0.25 mm can be any one of 60%, 65%, 70%, 75%, 80%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc., or within a range consisting of any two of them.

[0036] For example, in the matrix glass, the mass proportion of particles with a particle size less than 0.075 mm can be any one of 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 0%, etc., or within a range consisting of any two of them.

[0037] In some embodiments, in the matrix glass, particles with a diameter less than 0.075 mm account for 3%-5% by mass; and / or particles with a diameter of 0.09 mm to 0.25 mm account for 70%-80% by mass.

[0038] The sieving method can be used to calculate the mass fraction of particles of a specific particle size in the matrix glass. Specifically, the aperture corresponding to a 60-mesh sieve is 0.25mm, and the aperture corresponding to a 160-mesh sieve is 0.09mm. If the mass fraction of particles with a particle size of 0.09mm to 0.25mm is 70%-80%, then the mass fraction of particles that cannot pass through the 160-mesh sieve but can pass through the 60-mesh sieve (particle size 0.09mm to 0.25mm) is 70%-80%. The aperture corresponding to a 200-mesh sieve is 0.075mm. If the mass fraction of particles with a particle size less than 0.075mm is 3%-5%, then the mass fraction of particles that pass through the 200-mesh sieve is 3%-5%.

[0039] For example, in the mother particles, the mass proportion of particles with a particle size of less than 0.075 mm can be any one of 5%, 4%, 3%, etc., or within a range consisting of any two of them; and / or, the mass proportion of particles with a particle size of 0.09 mm to 0.25 mm can be any one of 70%, 72%, 75%, 78%, 80%, etc., or within a range consisting of any two of them.

[0040] Controlling the particle size of the matrix glass within the above range creates a well-balanced particle size distribution. This synergistic stacking effect of particles of varying sizes significantly increases the actual contact area between the nucleating agent and the matrix glass, promoting close and uniform adsorption of the nucleating agent onto the particle surfaces and interstices, significantly enhancing interfacial nucleation efficiency. Furthermore, a well-balanced particle size distribution shortens the ion diffusion path, accelerating material exchange and structural reorganization at the interface, further optimizing the kinetics of the nucleation process and effectively increasing both the nucleation rate and crystal growth rate.

[0041] In some embodiments, the particle size of the nucleating agent is less than 0.425 mm.

[0042] For example, the particle size of the crystal nucleating agent may be any one of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, etc., or within a range consisting of any two of them.

[0043] Controlling the particle size of the nucleating agent within the above range can promote the full mixing of the nucleating agent and the matrix glass, so that the nucleating agent can effectively and tightly adhere to the particle surface of the matrix glass, thereby significantly enhancing the nucleation induction efficiency of the nucleating agent on the matrix glass.

[0044] In some embodiments, the nucleating agent includes at least one of fluoride, phosphate, titanium dioxide, zirconium oxide, zircon sand, and chromium oxide, wherein the fluoride includes at least one of calcium fluoride, sodium fluorosilicate, magnesium fluoride, and sodium hexafluoroaluminate, and the phosphate includes at least one of calcium phosphate and ammonium dihydrogen phosphate.

[0045] The core function of the crystal nucleating agent is to induce crystallization. Specifically, the crystal nucleating agent itself acts as a crystallization center and combines with the cations (such as Ca 2+ 、Si 4+ ) produce strong interactions, forming an atomically ordered nucleation template at the interface. Simultaneously, by adjusting the chemical composition and microstructure of the nucleating agent, the formation of specific crystalline phases (such as wollastonite and diopside) can be induced, ultimately achieving precise control of the microstructure and properties of the glass-ceramics.

[0046] For example, fluorides include, but are not limited to, at least one of calcium fluoride (CaF2), sodium hexafluoroaluminate (Na3AlF6), sodium fluorosilicate (Na2SiF6), and magnesium fluoride (MgF2). Fluorides can separate from the melt during the crystallization process, forming fine crystalline precipitates and causing glass opacity. Utilizing the mechanism of fluoride opacifying glass, glass nucleation can be promoted, wherein the fluoride microcrystals are the nucleation centers of the glass. The nucleation temperature of fluoride is usually lower than the crystal growth temperature, so glass nucleated and crystallized with fluoride can form a large number of tiny crystals rather than a small number of coarse crystals. F - Radius (0.136nm) and O 2- The radius (0.14nm) is very close, so F - Can replace O 2- Without affecting the arrangement of ions in the glass structure too much. - It is -1, O 2- It is -2, so there are only two F - Replace an O 2- To achieve electrical neutrality. This is structurally equivalent to replacing one silicon-oxygen bond (≡Si-O-Si≡) with two silicon-fluorine bonds (≡Si-F). The presence of the Si-F group means a break in the silicon-oxygen network, weakening the glass structure and inducing crystallization.

[0047] For example, titanium dioxide (TiO2) is an intermediate cation in the glass structure. Under different conditions, it may exist in a hexacoordinated [TiO6] or tetracoordinated [TiO4] state. At high temperatures, due to the decrease in its coordination number, Ti 4+ It may participate in the silicon-oxygen network in a four-coordinated manner, thus being well miscible with the melt. As the temperature decreases, the four-coordinated titanium oxide [TiO4] transforms into a low-temperature stable state [TiO6]. Due to the structural differences between the two, TiO2 may separate from the silicon-oxygen network along with other RO-type oxides, forming nuclei and promoting the crystallization of the glass. In glass-ceramics using TiO2 as a nucleating agent, titanium-containing compounds, such as magnesium aluminum titanate, aluminum titanate, and magnesium titanate, are the first to precipitate. These titanium-containing compounds provide a substrate for the subsequent precipitation of equilibrium crystalline phases, promoting nucleation.

[0048] For example, zirconium oxide (ZrO2) can precipitate zirconium-rich crystals in the melt, thereby inducing nucleation of the parent glass. Specifically, in glass-ceramics with systems such as Li2O-Al2O3-SiO2 and MgO-Al2O3-SiO2, ZrO2 mainly induces the formation of a quartz solid solution as the primary crystalline phase and a fine-grained cubic ZrO2 solid solution as the secondary crystalline phase. It should be noted that ZrO2 has low solubility in silicate systems. For this reason, a small amount of phosphate can be introduced to promote the dissolution of ZrO2 in the glass melt.

[0049] For example, phosphates may include but are not limited to at least one of calcium phosphate and ammonium dihydrogen phosphate. The main active ingredient in phosphates is phosphorus pentoxide (P2O5), which is an oxide that can form a glass network and has good nucleation ability for silicate glass. Since P2O5 easily forms asymmetric phosphoric acid polyhedrons [PO4] in the silicon-oxygen network, and P 5+ Field strength is greater than Si 4+ , so it is easy to use with R + or R 2+ At the same time, it separates from the silicon-oxygen network. The reason why P2O5 nucleates the matrix glass is that it promotes phase separation, reduces interfacial energy, and lowers the activation energy of nucleation. Phosphates are often used in combination with titanium dioxide, zirconium oxide, and fluorides, or alone, in glass-ceramics based on Li2O-Al2O3-SiO2, Li2O-MgO-SiO2, and MgO-Al2O3-SiO2 systems. This not only helps enhance the nucleation of the matrix glass but also increases the nucleation rate, thereby producing finer-grained glass-ceramics.

[0050] In some embodiments, the crystal nucleating agent includes fluoride and phosphate, and the mass ratio of fluorine in the fluoride to phosphorus in the phosphate is (3.27-11.45):1.

[0051] For example, the mass ratio of fluorine in fluoride to phosphorus in phosphate can be 3.27:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11.45:1, and other typical but non-limiting values.

[0052] The composite system of fluoride and phosphate in the nucleating agent can achieve synergistic optimization of nucleation efficiency, crystal structure and material properties by regulating the mass ratio of fluorine element (F) and phosphorus element (P). Specifically, fluoride can promote the rapid phase separation of the glass phase during the crystallization process to form fluorine-rich micro-regions and phosphorus-rich micro-regions; then fluoride preferentially induces the formation of low-melting-point fluoride nuclei (such as fluorosilicate), while phosphate absorbs Ca through the strong polarity of PO bond. 2+ , Al3+ and other cations form a composite growth layer on the surface of the fluoride crystal nucleus, driving the crystal to develop to the micron scale and significantly improving the growth rate of the crystal nucleus.

[0053] In some embodiments, based on the total weight of the raw materials of the glass-ceramics being 100%, the raw materials include the following raw materials in percentage by weight:

[0054] Mother glass 80%-97%

[0055] Crystal nucleating agent 3%-20%.

[0056] The raw material components of microcrystalline glass are matrix glass and crystal nucleating agent with specific mass percentage. The crystal nucleating agent can give full play to the role of strongly inducing crystallization, promote the growth of crystals, and realize the effective crystallization of matrix glass.

[0057] In some embodiments, based on the total weight of the raw materials of the glass-ceramics being 100%, the raw materials include the following raw materials in percentage by weight:

[0058] Mother glass: 80%-97%;

[0059] Crystal nucleating agent: calcium fluoride 0.5%-10%, sodium fluorosilicate: 0-2%, calcium phosphate 1-7%, titanium dioxide 0-7%, quartz sand: 0-7%, chromium oxide 0-5%.

[0060] This system precisely controls the ratio of each raw material to fully stimulate the induced crystallization efficiency of the nucleating agent (such as calcium fluoride, sodium fluorosilicate, calcium phosphate, etc.), so that the microcrystalline glass can achieve efficient crystallization and microstructural optimization during the crystallization process, giving the microcrystalline glass both excellent mechanical properties and chemical stability.

[0061] In some embodiments, based on the total weight of the raw materials of the glass-ceramics being 100%, the raw materials include the following raw materials in percentage by weight:

[0062] Mother glass: 80%-97%;

[0063] Nucleating agent: calcium fluoride 2%-9%, sodium fluorosilicate 1%-2%, calcium phosphate 1%-6%, titanium dioxide 0.2%-3%, zircon sand 0.2%-2%, chromium oxide 0.2%-3%.

[0064] For example, the weight percentage of the matrix glass may be 80%, 82%, 85%, 88%, 90%, 92%, 95%, 97%, etc., which are typical but non-limiting values.

[0065] For example, the weight percentage of calcium fluoride may be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc., which are typical but non-limiting values.

[0066] For example, the weight percentage of sodium fluorosilicate may be 1.1%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or other typical but non-limiting values.

[0067] For example, the weight percentage of calcium phosphate can be 1%, 2%, 3%, 4%, 5%, 6%, etc., which are typical but non-limiting values.

[0068] For example, the weight percentage of titanium dioxide may be 0.2%, 0.5%, 1%, 2%, 3%, etc., which are typical but non-limiting values.

[0069] For example, the weight percentage of zircon sand may be 0.2%, 0.5%, 1%, 1.5%, 2%, and other typical but non-limiting values.

[0070] For example, the weight percentage of chromium oxide may be 0.2%, 0.5%, 1%, 2%, 3%, etc., which are typical but non-limiting values.

[0071] By controlling the raw material components and their mass percentages of microcrystalline glass within the above ranges, calcium fluoride, calcium phosphate, titanium dioxide, zircon sand, chromium oxide, and other nucleating agents can form a good synergistic system with the matrix glass. During the nucleation stage, calcium fluoride breaks the silicon-oxygen network structure of soda-lime glass by releasing fluoride ions, significantly reducing the viscosity of the glass phase and creating conditions for the rapid diffusion of other nucleating agents; calcium phosphate, with its phosphorus-oxygen tetrahedral structure, provides stable heterogeneous nucleation sites, effectively increasing the density of the nuclei. At the same time, titanium dioxide can increase the local order of the nuclei, further reducing the nucleation activation energy and assisting in the formation of nanoscale initial nuclei; zircon sand slowly releases zirconium ions at high temperatures, combining with calcium ions and oxygen ions in the glass to form a high-temperature resistant nucleus precursor; and chromium oxide optimizes the uniformity of the nucleus distribution by adjusting the surface tension of the melt. During the crystallization phase, multiple nucleating agents work synergistically: calcium phosphate and calcium fluoride continue to guide crystal growth along specific directions, titanium dioxide regulates the growth rate through adsorption to crystal surfaces, and zircon sand and chromium oxide promote uniform distribution of the crystal phase. Together, these components guide crystal growth, forming a uniformly sized and evenly distributed crystalline structure. The resulting glass-ceramics not only inherit the processing advantages of soda-lime glass but also possess higher mechanical strength (flexural strength of 86.3 MPa and compressive strength of 430 MPa).

[0072] In some embodiments, the raw material of the glass-ceramics further includes a binder, and based on the total weight of the raw material of the glass-ceramics being 100%, the content of the binder is 0.5%-2%.

[0073] For example, the binder content may be 0.5%, 1%, 1.5%, 2%, etc., which are typical but non-limiting values.

[0074] During the process of mixing the matrix glass and the crystal nucleating agent to form a blank, the introduction of a binder can make the matrix glass particles and the crystal nucleating agent fit tightly together through interfacial adsorption and bridging, forming a blank with significantly improved density.

[0075] In some embodiments, the binder includes at least one of sodium silicate and an organic alcohol amine lipid binder. For example, the organic alcohol amine lipid binder includes but is not limited to terpineol.

[0076] A second aspect of the present invention provides a method for preparing glass-ceramics, comprising the following steps:

[0077] Step S10: providing raw material components according to the glass-ceramics provided in the first aspect;

[0078] Step S20: mixing the mother glass and the crystal nucleating agent to obtain a mixed material, wherein the particle size of the mixed material is less than 0.425 mm;

[0079] Step S30, shaping the mixed material to obtain a green body;

[0080] Step S40: crystallize the green body to obtain glass-ceramics.

[0081] The preparation method of the microcrystalline glass provided in the second aspect of the embodiment of the present application adopts the processing technology of "mixing treatment-molding blank-crystallization treatment": first, the matrix glass and the crystal nucleating agent are mixed, then the blank is obtained by molding treatment, and finally the microcrystalline glass is obtained by crystallization treatment. On the one hand, the crystal nucleating agent is more evenly distributed between the particles of the matrix glass through the mixing treatment, which significantly improves the fit between the two. In the subsequent crystallization treatment process, the crystal nucleating agent can serve as a nucleation site, increase the interface nucleation ability of the matrix glass, and promote the uniform formation of crystals inside the matrix glass. At the same time, the evenly distributed crystal nucleating agent can also inhibit the excessive aggregation of crystal nuclei in local areas, reduce the risk of uneven grain size due to spatial competition during crystal growth, promote the uniform germination and orderly growth of crystal nuclei inside the matrix glass, and help to obtain microcrystalline glass with uniform microstructure and excellent mechanical properties. glass; on the other hand, the mixed material obtained after the mixing process has a specific particle size, specifically, the particle size is less than 0.425 mm. The smaller particle size gives it a significantly increased specific surface area and higher surface free energy, which greatly improves the reactivity of the mixed material. In the subsequent crystallization process, the interface reaction efficiency between the nucleating agent and the matrix glass is greatly improved, which not only accelerates the induction and growth of the crystal nucleus, but also promotes the uniform transformation of the crystal phase through efficient material transfer and energy exchange, thereby realizing rapid and efficient crystallization of the matrix glass, significantly shortening the preparation cycle and improving the quality of the finished product.

[0082] In some embodiments, in step S10, the selection and addition amounts of the raw material components are as described above and will not be repeated here.

[0083] In some embodiments, in step S20, the mother glass and the crystal nucleating agent are mixed to obtain a mixed material in the following specific process:

[0084] The matrix glass and the crystal nucleating agent are mixed and then ground to obtain a mixed material.

[0085] Grinding can be performed using methods well known to those skilled in the art. For example, a grinding vessel lining made of alumina or zirconia can be used, along with grinding balls made of the same material. These materials offer high hardness and wear resistance, effectively preventing the introduction of impurities during grinding while ensuring grinding efficiency and uniform particle size.

[0086] In some embodiments, in step S30, the process of molding the mixed material to obtain a green body may also be:

[0087] The mixed material and the binder are mixed and then molded to obtain a green body.

[0088] In some embodiments, in step S30 , the molding process includes mold pressing or extrusion molding.

[0089] In some embodiments, in step S40, the crystallization process includes a nucleation stage and a crystallization stage. The conditions of the nucleation stage include: a temperature of 590°C-710°C and a time of 0.5h-3h; the conditions of the crystallization stage include: a temperature of 780°C-850°C and a time of 0.8h-5h.

[0090] For example, the temperature of the nucleation stage can be typical but non-limiting values ​​such as 590°C, 610°C, 630°C, 650°C, 680°C, 710°C, etc., and the time can be typical but non-limiting values ​​such as 0.5h, 1h, 2h, 3h, etc.

[0091] For example, the temperature in the crystallization stage can be typical but non-limiting values ​​such as 780°C, 800°C, 820°C, and 850°C, and the time can be typical but non-limiting values ​​such as 0.8h, 1h, 2h, 3h, 4h, and 5h.

[0092] The crystallization treatment adopts a staged temperature control process. By regulating the temperature and time range of the nucleation stage and the crystallization stage, the nucleation efficiency of the microcrystalline glass and the growth rate of the crystal can be effectively improved, and the uniform transformation of the crystal phase can be promoted, which helps to obtain microcrystalline glass with uniform microstructure and excellent mechanical properties.

[0093] The following describes the details in conjunction with specific embodiments.

[0094] Example 1

[0095] This embodiment provides a glass-ceramic and a method for preparing the same.

[0096] A glass-ceramic comprising the following raw material components in percentage by weight, based on the total weight of raw materials of the glass-ceramic being 100%:

[0097] Matrix glass: 91.4%;

[0098] Nucleating agent: calcium fluoride 6%, calcium phosphate 2%;

[0099] Binder (selected from sodium silicate): 0.6%.

[0100] The matrix glass is soda-lime glass obtained by the float plate process, and its particle size distribution is as follows:

[0101] The particle size of the matrix glass particles is less than or equal to 2 mm; the mass proportion of particles with a particle size less than 0.075 mm is 5%, the mass proportion of particles with a particle size greater than or equal to 0.075 mm and less than 0.09 mm is 10%; the mass proportion of particles with a particle size of 0.09 mm to 0.25 mm is 75%, and the mass proportion of particles with a particle size greater than 0.25 mm and less than 2 mm is 5%.

[0102] A method for preparing glass-ceramics comprises the following steps:

[0103] Step 1: Mix and grind the mother glass with calcium fluoride and calcium phosphate to obtain a mixture, and the mixture can pass through a 40-mesh sieve (the particle size of the mixture is less than 0.425 mm).

[0104] Step 2: Mix the mixed material and the binder, press them together to form a sheet, and obtain a green body.

[0105] Step 3: Place the blank in a muffle furnace and heat it to 650°C and keep it for 1 hour for nucleation, then heat it to 850°C and keep it for 2 hours for crystallization, then cool it down and anneal it to room temperature to obtain microcrystalline glass.

[0106] Examples 2-5

[0107] Examples 2-5 provide a glass-ceramic and a preparation method thereof. These differ from Example 1 primarily in at least one of the following: the selection and amount of a nucleating agent, the selection and amount of a binder, the selection and particle size distribution of the matrix glass, the nucleation conditions, and the crystallization conditions. See Table 1 for details.

[0108] Table 1

[0109]

[0110] In Table 1:

[0111] Granularity A means:

[0112] The particle size of the matrix glass particles is less than or equal to 2 mm; the mass proportion of particles with a particle size less than 0.075 mm is 5%, the mass proportion of particles with a particle size greater than or equal to 0.075 mm and less than 0.09 mm is 10%; the mass proportion of particles with a particle size of 0.09 mm to 0.25 mm is 75%, and the mass proportion of particles with a particle size greater than 0.25 mm and less than 2 mm is 5%.

[0113] Granularity B means:

[0114] The particle size of the matrix glass particles is less than or equal to 2 mm; the mass of particles with a particle size less than 0.075 mm accounts for 8%; the mass of particles with a particle size of 0.09 mm to 0.25 mm accounts for 75%; the mass of particles with a particle size greater than 0.25 mm and less than 2 mm accounts for 7%.

[0115] Fluorine:phosphorus represents the mass ratio of the fluorine element contained in the crystal nucleus agent to the phosphorus element contained in the crystal nucleus agent.

[0116] The raw material components contained in float glass and daily bottles and cans are shown in Table 2.

[0117] Table 2

[0118]

[0119] Comparative Example

[0120] Comparative Examples 1-3 provide a glass-ceramic and a preparation method thereof. These differ from Example 1 primarily in at least one of the following: the selection and amount of a nucleating agent, the selection and amount of a binder, the selection and particle size distribution of the matrix glass, the nucleation conditions, and the crystallization conditions. See Table 3 for details.

[0121] Table 3

[0122]

[0123]

[0124] In Table 3:

[0125] Granularity A means:

[0126] The particle size of the matrix glass particles is less than or equal to 2 mm; the mass proportion of particles with a particle size less than 0.075 mm is 5%, the mass proportion of particles with a particle size greater than or equal to 0.075 mm and less than 0.09 mm is 10%; the mass proportion of particles with a particle size of 0.09 mm to 0.25 mm is 75%, and the mass proportion of particles with a particle size greater than 0.25 mm and less than 2 mm is 5%.

[0127] Fluorine:phosphorus represents the mass ratio of the fluorine element contained in the crystal nucleus agent to the phosphorus element contained in the crystal nucleus agent.

[0128] The preparation method of the microcrystalline glass in the above comparative examples 1-2 is the same as that in Example 1 and will not be repeated here.

[0129] The preparation method of the glass-ceramics in Comparative Example 3 is as follows:

[0130] Step 1: Mix and grind the mother glass with calcium fluoride and calcium phosphate to obtain a mixture, wherein the mixture can pass through an 8-mesh sieve but cannot pass through a 10-mesh sieve (the particle size of the mixture is about 2.36 mm).

[0131] Step 2: Mix the mixed material and the binder, press them together to form a sheet, and obtain a green body.

[0132] Step 3: Place the blank in a muffle furnace and heat it to 650°C and keep it for 1 hour for nucleation, then heat it to 850°C and keep it for 2 hours for crystallization, then cool it down and anneal it to room temperature to obtain microcrystalline glass.

[0133] Performance Testing

[0134] According to JC / T 872-2019 “Microcrystalline glass for architectural decoration”, the performance of the microcrystalline glass prepared in Examples 1-5 and Comparative Examples 1-3 was tested, and the test results are shown in Tables 4 and 5.

[0135] Table 4

[0136] Example 1 Example 2 Example 3 Example 4 Example 5 <![CDATA[Density (g / cm 3 )]]> 2.58 2.52 2.55 2.57 2.59 Mohs hardness 6 6 6.5 6.5 6 Water absorption (%) 0.5 0.3 0.5 0.5 0.4 <![CDATA[Coefficient of expansion (×10 -7 )]]> 93 93 89 85 87 Compressive strength (MPa) 460 380 430 480 420 Flexural strength (MPa) 86.3 79 81.3 90 87.5 color Pure white beige grass green grass green dark green Glossiness 91 93 89 88 85

[0137] Table 5

[0138] Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Density (g / cm 3 )]]> 2.48 2.57 2.51 Mohs hardness 5.5 6 5.5 Water absorption (%) 0.5 0.3 1 <![CDATA[Coefficient of expansion (×10 -7 )]]> 95 87 92 Compressive strength (MPa) 180 430 350 Flexural strength (MPa) 26.3 56.3 51 color Pure white Jute dots Pure white Glossiness - 88 85

[0139] It can be seen from the data in Tables 4 and 5 that, compared with Comparative Examples 1-2, the glass-ceramics provided in the examples of the present application show better performance in terms of hardness, density, impermeability and mechanical strength. Specifically, in combination with the examples and comparative examples 1-2, it can be seen that the glass-ceramics provided in comparative example 1 has poor gloss and significantly low mechanical properties. Taking specific data as an example, its compressive strength is only 180 MPa and its flexural strength is only 26.3 MPa. The glass-ceramics provided in comparative example 2 has insufficient dimensional stability and poor mechanical properties. For example, its flexural strength is only 53.3 MPa.

[0140] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A glass-ceramic, characterized in that: The microcrystalline glass comprises a product formed by mixing mother glass and a crystal nucleating agent to form a blank and then undergoing a crystallization treatment; The particle size of the matrix glass particles is less than or equal to 2 mm, the mass of particles with a particle size less than 0.075 mm accounts for less than 10%, and the number of particles with a particle size of 0.09 mm-0.25 mm accounts for more than 60%.

2. The glass-ceramic according to claim 1, wherein In the matrix glass, particles with a particle size of less than 0.075 mm account for 3% to 5% by mass; and / or particles with a particle size of 0.09 mm to 0.25 mm account for 70% to 80% by mass.

3. The glass-ceramic according to claim 1, wherein: The particle size of the crystal nucleating agent is less than 0.425 mm; and / or, The crystal nucleating agent includes at least one of fluoride, phosphate, titanium dioxide, zirconium oxide, zircon sand, and chromium oxide, wherein the fluoride includes at least one of calcium fluoride, sodium fluorosilicate, magnesium fluoride, and sodium hexafluoroaluminate; and the phosphate includes at least one of calcium phosphate and ammonium dihydrogen phosphate.

4. The glass-ceramic according to claim 3, wherein: The crystal nucleating agent includes fluoride and phosphate, and the mass ratio of the fluorine element in the fluoride to the phosphorus element in the phosphate is (3.27-11.45):

1.

5. The glass-ceramic according to any one of claims 1 to 4, characterized in that: Taking the total weight of the raw materials of the glass-ceramics as 100%, the raw material components are as follows in percentage by mass: Mother glass 80%-97% Nucleating agent 3%-20%.

6. The glass-ceramic according to any one of claims 1 to 4, characterized in that: Taking the total weight of the raw materials of the glass-ceramics as 100%, the raw material components are as follows in percentage by weight: Mother glass: 80%-97%; Crystal nucleating agent: calcium fluoride 0.5%-10%, sodium fluorosilicate: 0-2%, calcium phosphate 1-7%, titanium dioxide 0-7%, quartz sand: 0-7%, chromium oxide 0-5%.

7. The glass-ceramic according to claim 6, wherein: Taking the total weight of the raw materials of the glass-ceramics as 100%, the raw material components are as follows in percentage by weight: Mother glass: 80%-97%; Nucleating agent: calcium fluoride 2%-9%, sodium fluorosilicate 1%-2%, calcium phosphate 1%-6%, titanium dioxide 0.2%-3%, zircon sand 0.2%-2%, chromium oxide 0.2%-3%.

8. The glass-ceramics according to any one of claims 1 to 4, characterized in that The raw materials of the microcrystalline glass also include a binder, and the content of the binder is 0.5%-2% based on the total weight of the raw materials of the microcrystalline glass as 100%; and / or the binder includes at least one of sodium silicate and organic alcohol amine lipid binders.

9. A method for preparing glass-ceramics, characterized in that: The following steps are involved: The glass-ceramic according to any one of claims 1 to 8, providing raw material components; The mother glass and the crystal nucleating agent are mixed to obtain a mixed material, wherein the particle size of the mixed material is less than 0.425 mm; Molding the mixed material to obtain a green body; The green body is crystallized to obtain glass-ceramics.

10. The method for preparing glass-ceramics according to claim 9, wherein: The crystallization treatment includes a nucleation stage and a crystallization stage, wherein the conditions of the nucleation stage include: a temperature of 590° C. to 710° C. and a time of 0.5 h to 3 h; the conditions of the crystallization stage include: a temperature of 780° C. to 850° C. and a time of 0.8 h to 5 h; and / or, The molding process includes die pressing or extrusion molding.